Penerapan Layanan Bimbingan Dan Konseling Pada Anak Usia Dini Di Tk Al-Fikri School - Indah Afrilia Hasibuan; Mutiara Alya Hasyim; Ririn Widayanti; Fauziah Nasution (Peneliti.net, 2023)
This study aims to explore and analyze the application of guidance and counseling services to early childhood at Al-Fikri School Kindergarten. The focus of this study was to evaluate the effectiveness of the guidance and counseling strategies applied in assisting the emotional, social and academic development of young children at the school. This study used a qualitative approach, which allowed the researcher to gain an in-depth understanding of the experiences and perspectives of the participants. The research method used is qualitative research, which involves collecting data through observation, interviews, and analysis of documents related to the guidance and counseling program at TK Al-Fikri School. Participatory observation was carried out to directly observe the interactions between counselors, teachers, and children in the context of guidance and counseling. Interviews were conducted with counselors, teachers and parents involved in guidance and counseling services to gain insight into their experiences, their views on the effectiveness of the services, and the role they play in supporting children's development. In addition, document analysis was carried out to study policies, programs and resources related to guidance and counseling in TK Al-Fikri School. The data collected is then analyzed thematically, in which common patterns and themes are identified from the collected data. The results of this study will provide a better understanding of the effectiveness of guidance and counseling strategies implemented in TK Al-Fikri School, as well as the contributions made by counselors, teachers and parents in supporting early childhood development. This research is expected to provide valuable insights for Kindergarten Al-Fikri School and other educational institutions in developing and improving guidance and counseling services for early childhood. The findings and recommendations of this research can be used as a basis for improving and optimizing existing services, including increased training for counselors, active involvement of parents, and collaboration with related professionals. Thus, this research can contribute to efforts to improve the emotional, social, and academic development of early childhood at Al-Fikri School Kindergarten and other schools.